Um retrato da Sepse Neonatal tardia no Médio Xingu - SILVA, Ana Beatriz Costa da (2025)
Introduction: Neonatal sepsis is a clinical syndrome responsible for high mortality rates in newborns (NB) annually in various countries. In Brazil, it is estimated that around 60% of infant mortality occurs in the neonatal period, with sepsis being one of the main causes. Numerous factors contribute to the high mortality related to neonatal sepsis, including delays in the identification and treatment of NB, delayed home seeking of specialized care, and lack of access to adequately trained professionals. Objective: To investigate cases of late-onset neonatal sepsis admitted to the Neonatal Intensive Care Unit (NICU) of the Public Regional Hospital of Transamazônica (HRPT) from 2018 to 2020. Methodology: The study was cross-sectional, with a descriptive nature, encompassing NB treated at HRPT. The sample consisted of 35 individuals, all with late-onset neonatal sepsis identified during the study period, according to ANVISA criteria. Newborns who died within the first 24 hours of admission or before 72 hours of life, those with symptomatic congenital infection, and cases with insufficient information were excluded. Results: The prevalence of late-onset neonatal sepsis was 11.55%. Additionally, 16 patients progressed to death, showing a lethality rate of 47.7% in the total population of NB included in the study. Furthermore, in multivariate analysis, there was a significant association between death and mechanical ventilation (p=0.014) and death and days of mechanical ventilation use (p=0.04). Conclusion: The present study found that sepsis is a significant cause of death in hospitalized newborns, especially in premature infants. It is also noteworthy that the microbiological profile of the unit is similar to that of poor countries.